THE SCIENTIFIC AND PEDAGOGICAL IMPORTANCE OF INTEGRATING ECOLOGICAL CULTURE AND THE SUSTAINABLE DEVELOPMENT GOALS INTO ENVIRONMENTAL EDUCATION AND UPBRINGING (World Bulletin of Social Sciences, 2026)
This article examines the importance of integrating ecological culture and the Sustainable Development Goals (SDGs) into the education system. It highlights the pedagogical and social significance of environmental awareness, sustainability-oriented values, and interdisciplinary learning in contemporary education